2012
DOI: 10.1039/c2ob07170c
|View full text |Cite
|
Sign up to set email alerts
|

Tunnelling control of chemical reactions – the organic chemist's perspective

Abstract: Even though quantum mechanical tunnelling has been appearing recurrently mostly in theoretical studies that emphasize its decisive role for many chemical reactions, it still appears suspicious to most organic chemists. Recent experiments in combination with powerful computational approaches, however, have demonstrated that tunnelling must be included to fully understand chemical reactivity. Here we provide an overview of the importance of tunnelling in organic chemical reactions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
194
0
5

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 158 publications
(205 citation statements)
references
References 89 publications
(94 reference statements)
6
194
0
5
Order By: Relevance
“…For the second criterion, the ratio A H /A D was 0.28 (A H = 97.9, A D = 344.2), much less than 0.7, which implies tunneling. This suggestion is supported by ample precedent for tunneling in 1,2-H shifts, particularly in carbenes (17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27), and also in cyclopentadienes (14). The barriers in these reactions vary from ca.…”
Section: Methodsmentioning
confidence: 66%
“…For the second criterion, the ratio A H /A D was 0.28 (A H = 97.9, A D = 344.2), much less than 0.7, which implies tunneling. This suggestion is supported by ample precedent for tunneling in 1,2-H shifts, particularly in carbenes (17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27), and also in cyclopentadienes (14). The barriers in these reactions vary from ca.…”
Section: Methodsmentioning
confidence: 66%
“…Moreover, Oba et al (2012) concluded that a tunnel effect is responsible for the H abstraction of H 2 by OH radicals resulting in the formation of water molecules in astrophysical conditions. The importance of the tunnel effect in chemistry is discussed in more than one review (Ley et al 2012;Schreiner et al 2011) as well as for its implication in the surface reactions happening in an astrochemical context (Hama & Watanabe 2013;Trixler 2013;Reboussin et al 2014). Our study demonstrates that H 2 can be a source of hydrogenation of CN radicals, but since we are using VUV to generate CN radicals, kinetic studies to confirm tunneling reaction are not possible.…”
Section: Astrophysical Implicationsmentioning
confidence: 99%
“…a) Electronic mail: jeremy.richardson@phys.chem.ethz.ch Quantum tunneling effects have been measured in atmospheric and astrochemistry, 7,8 as well as organic chemistry at low temperatures. 9 In some cases, they can change the mechanism for the reaction and hence the selectivity of the products. 10 On surfaces, one can directly observe tunneling events such as the hopping of atoms between sites 11 or the rearrangement of a molecular cluster.…”
Section: Introductionmentioning
confidence: 99%